2009
DOI: 10.5296/rae.v1i1.186
|View full text |Cite
|
Sign up to set email alerts
|

Joint Impact of the Dimensions of Governance and Economic Freedom on Economic Growth in O.E.C.D. Nations: An Analysis with Controls for Budget Deficits and G8 Status

Abstract: This study examines the impact of various forms of economic freedom and various dimensions of governance, as well as a number of economic factors, on economic growth among O.E.C.D. nations. The study period runs from 2004 through 2007. The study adjusts for status as a G8 nation and for budget deficits. Panel least squares estimation finds that the natural log of per capita purchasing-power-parity adjusted real GDP in O.E.C.D. nations is positively impacted by business freedom, monetary freedom, trade freedom,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The results show that a onepercentage point increase in corruption is associated with a 0.124 percentage point decline in governance. Cebula and Ekstrom (2009) investigate different forms of economic freedom and dimensions of governance to gauge their impact on growth in OECD countries between 2004 and 2007, while adjusting for G8 status and budget status. They use five forms of economic freedom, with trade freedom as an interesting addition to earlier investigations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that a onepercentage point increase in corruption is associated with a 0.124 percentage point decline in governance. Cebula and Ekstrom (2009) investigate different forms of economic freedom and dimensions of governance to gauge their impact on growth in OECD countries between 2004 and 2007, while adjusting for G8 status and budget status. They use five forms of economic freedom, with trade freedom as an interesting addition to earlier investigations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper contributes to two strands of the literature: (i) the current debate on the role of governance quality in growth (see Acemoglu et al, 2002Acemoglu et al, , 2004Bhattacharyya, 2009;North, 1991) and (ii) macroeconomic studies of the relationship between governance and total factor productivity (TFP) (Olson et al, 2000). While the literature shows that governance has a positive impact on economic growth (see Kaufmann & Kraay, 2002;Cebula & Ekstrom, 2009), to our knowledge there is no existing study on the relationship between governance, average labor productivity growth and TFP growth for Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as property rights, business freedom and freedom from corruption also contributed to economic prosperity. Cebula & Elkstrom (2009) evaluated countries in the Organisation for Economic Co-Operation and Development (OECD) between 2004 and 2007 (p. 2). Results indicated that economic growth was greater in countries with higher levels of trade and business freedom, monetary freedom and secure systems of property rights protection (Cebula & Elkstrom, 2009, p. 7).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the political effect, Costalli et al (2017) showed the economic cost of ethnic fractionalization of 20 war countries that experienced an average annual loss of GDP per capita exceeding 17%. Cebula and Ekstrom (2009) investigated the effect of economic factors OECD countries between 2004 and 2007. Their findings indicated that economic growth increases for higher levels of trade, business and monetary freedom, and protection of property rights.…”
Section: Literature Reviewmentioning
confidence: 99%